Assessment on Heck-Immine Derivatives as Organic Semiconductor Materials - Rahamathullah, Rafizah; Keemi, Lim; Khairul, Wan M. (Makara Journal of Technology, 2017)
This paper reports the synthetic, characterization and theoretical evaluation of new class of hybrid Heck-immine system involving mixed moieties of vinylene (C=C) and azomethines (CH=N) which has been successfully integrated into an addition of organic semiconducting materials. The assessment of 4-[(hexyloxyphenyl)methylene]amino)-4’-chloro-stilbene (HEXCS) based on Donor (D)-π-Acceptor (A) was evaluated as active semiconductor material candidates via several spectroscopic and analytical techniques. In turn, the investigation of its potential as dopant system in conductive film was successfully deposited on indium tin oxide (ITO) coated substrate via spin coating method. The relationship between electronic and optical properties, chemical modelling at molecular interactions and electrical performances of the designated system were evaluated. In addition, the quantum mechanical calculation proved that the value of energy separation of HEXCS between HOMO and LUMO exhibits 3.09 eV which was in good agreement with the experimental result of optical band gap 3.10 eV. The findings from the thermal and conductivity analysis revealed that the developed film HEXCS exhibited good stability at high temperature and electrical performance with an increasing conductivity up to 0.1531 Scm-1 under maximum light intensity of 100 Wm-2. Therefore, this proposed type of molecular framework has given an ideal indication to act as semiconductor material candidates potentially use in any designated electronic application.